2010
DOI: 10.1111/j.1365-2621.2010.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of treatments to retard browning of fresh-cut Russet potato with emphasis on controlled atmospheres and low concentrations of bisulphite

Abstract: The cultivar Pacific Russet with high browning susceptibility was used for most testing. Controlled atmospheres (0.3%, 3% and 21% O 2 in combination with 0%, 6% or 12% CO 2 ) and anti-browning chemicals were studied in relation to quality retention and wound-induced phenolic metabolism of fresh-cut slices for up to 16 days at 5°C. The 3% O 2 + 12% CO 2 atmosphere was most effective among those tested, and retarded increases in phenolics and phenylalanine ammonia lyase activity, but had only slight benefit on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
2
32
0
4
Order By: Relevance
“…Se ha reportado que la preparación de lechuga como producto fresco cortado (fresca, troceada y empacada) induce cambios fisiológicos y bioquímicos que incluyen daños en paredes celulares y tejidos (Zhan et al, 2009;Wagstaff et al, 2010), incremento en ritmo respiratorio y producción de etileno, inducción de síntesis de metabolitos secundarios, activación de mecanismos defensivos (Ma et al, 2010), y disrupción de membranas (González y Barret, 2010). Asimismo, los productos frescos troceados en general sufren pérdida de la estructura celular durante las operaciones de corte, lo cual permite interactuar a la polifenol oxidasa (PPO) con compuestos fenólicos oxidables presentes naturalmente en el producto, causando oscurecimiento de las superficies cortadas (González y Barret, 2010).…”
Section: Introductionunclassified
See 3 more Smart Citations
“…Se ha reportado que la preparación de lechuga como producto fresco cortado (fresca, troceada y empacada) induce cambios fisiológicos y bioquímicos que incluyen daños en paredes celulares y tejidos (Zhan et al, 2009;Wagstaff et al, 2010), incremento en ritmo respiratorio y producción de etileno, inducción de síntesis de metabolitos secundarios, activación de mecanismos defensivos (Ma et al, 2010), y disrupción de membranas (González y Barret, 2010). Asimismo, los productos frescos troceados en general sufren pérdida de la estructura celular durante las operaciones de corte, lo cual permite interactuar a la polifenol oxidasa (PPO) con compuestos fenólicos oxidables presentes naturalmente en el producto, causando oscurecimiento de las superficies cortadas (González y Barret, 2010).…”
Section: Introductionunclassified
“…It has been reported that the preparation of lettuce as a freshcut product (fresh cut and packaged) induces biochemical and physiological changes which include damage to cellular walls and tissues (Zhan et al, 2009;Wagstaff et al, 2010), increased respiration rate and ethylene production, induction of secondary metabolite synthesis, activation of defense mechanisms (Ma et al, 2010), and disruption of membranes (González and Barrett, 2010). Additionally, cut fresh products generally suffer loss of cellular structure during cutting operations, which allows polyphenol oxidase (PPO) to interact with oxidized phenolic compounds naturally present in the product, causing browning of the cut surfaces (González and Barret, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…hOsOda and co-workers (2003) showed the effect of 0.05 and 0.2% of OEO as an antibrowning treatment in shredded lettuce, observing 20 and 70.4% of browning inhibition, respectively. The treatment of potato slices with sodium bisulphite 0.25% and ascorbic acid 1.25% + citric acid 1.25% in combination with controlled atmospheres showed no efficacy inhibiting PPO activity during storage (Ma et al, 2010).…”
Section: Browning Index and Ppo Activitymentioning
confidence: 90%